2012
DOI: 10.1128/jcm.06243-11
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonamide Resistance in Isolates of Nocardia spp. from a U.S. Multicenter Survey

Abstract: f Recent reports of increasing in vitro sulfonamide resistance in Nocardia prompted us to investigate the findings. Despite the reports, there is a paucity of clinical reports of sulfonamide failure in treatment of nocardia disease. We reviewed 552 recent susceptibilities of clinical isolates of Nocardia from six major laboratories in the United States, and only 2% of the isolates were found to have resistant MICs of trimethoprim-sulfamethoxazole and/or sulfamethoxazole. We hypothesize that the discrepancies i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
90
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 16 publications
7
90
1
2
Order By: Relevance
“…Particularly, it is not known how many patients were treated successfully with sulfonamides. In contrast, in an additional retrospective study of sulfonamide susceptibility results of 552 recent clinical Nocardia isolates from various regions of the United States, Brown-Elliott et al reported only 2% of isolates to have MICs reported indicating resistance to trimethoprim-sulfamethoxazole or sulfamethoxazole (1). Given the data presented by Brown-Elliott et al and our own data demonstrating the difficulty of sulfonamide susceptibility test interpretation with these organisms, we are concerned that the in vitro results reported by these Uhde et al may not accurately reflect in vivo responsiveness.…”
Section: Discussionmentioning
confidence: 87%
“…Particularly, it is not known how many patients were treated successfully with sulfonamides. In contrast, in an additional retrospective study of sulfonamide susceptibility results of 552 recent clinical Nocardia isolates from various regions of the United States, Brown-Elliott et al reported only 2% of isolates to have MICs reported indicating resistance to trimethoprim-sulfamethoxazole or sulfamethoxazole (1). Given the data presented by Brown-Elliott et al and our own data demonstrating the difficulty of sulfonamide susceptibility test interpretation with these organisms, we are concerned that the in vitro results reported by these Uhde et al may not accurately reflect in vivo responsiveness.…”
Section: Discussionmentioning
confidence: 87%
“…Recent reports showed that 2% to 43% of Nocardia species were resistant to TMP/SMX (11). The duration of treatment is generally prolonged to minimize the risk of disease relapse.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal antimicrobial treatment regimens have not been firmly established (7). TMP/SMX is most commonly used to treat nocardiosis (7,11). Alternative antimicrobial agents with activity against Nocardia species include AMK, IPM, meropenem, ceftriaxone, cefotaxime, MINO, moxifloxacin, levofloxacin, linezolid, tigecycline, and amoxicillin-clavulanic acid (7).…”
Section: Discussionmentioning
confidence: 99%
“…Previously identified species have been reclassified as species complexes encompassing multiple species, and numerous novel Nocardia species have been identified (5). Currently, 87 species are enumerated in the List of Prokaryotic Names with Standing in Nomenclature (LPSN) (http://www.bacterio.net/nocardia.html), many of which are clinically significant (1).However, data on antimicrobial susceptibility has lagged behind the advances in taxonomy, with only a few reports providing recent data on newer antimicrobials (4,6,7,8,9,10,11,12,13). These reports largely focus on the species traditionally associated with clinical infections, such that antimicrobial susceptibility data are not available for a large number of newly identified, but clinically relevant, Nocardia species that are isolated less frequently in the clinical laboratory.…”
mentioning
confidence: 99%